Planejamento e estudo in silico de derivados de 6-gingerol como inibidores de acetilcolinesterase comparados a donepezila (Revista Brasileira Multidisciplinar, 2022)
Alzheimer's disease (AD) is currently one of the most studied dementias due to the increase of cases over the years. Acetylcholinesterase (AChE) inhibitors have been widely studied to obtain new drug candidates to combat AD. In this sense, new derivatives of the natural product 6-gingerol were planned and analyzed against the inhibition of the acetylcholinesterase enzyme in silico and its prediction on the Absorption, Distribution, Metabolism, Elimination and Toxicity (ADMET) model. Using molecular modeling tools to minimize the structures of the studied compounds and then verify the interactions of these derivatives in comparison with the standard donepezyl, due to its structural similarity, with the AChE enzyme. The results showed that two compounds have the best in silico interactions and the best ADMET properties for a good drug that can act on the Central Nervous System.